Labyrinthine Structure with Subwavelength and Broadband Sound Insulation - Heng Jiang; Yu Liu; Wenshuai Xu; Tao Yang; Dongliang Pei; Meng Chen; Yuren Wang (Shock and Vibration)
In this text, the combination of spiral structure and zigzag channels is introduced to design labyrinthine structures, in which sound waves can propagate alternately in the clockwise and counterclockwise directions. Finite element method and S-parameter retrieval method are used to calculate band structures, effective parameters, and transmission properties of the structures. The influences of different structural parameters on their acoustic properties are also studied. These results show labyrinthine structures have multiple bandgaps in the range of 0 Hz–1000 Hz, and the proportion of bandgaps exceeds 33%, which indicates labyrinthine structures have good broadband properties. The normalized frequency of the lowest bandgaps is far smaller than 1, which indicates the structures take good control of sound waves on subwavelength scale. Combining units with different structural parameters can achieve better sound insulation. This research provides a new kind of space-coiling structure for low-frequency and broadband sound waves control, which have excellent application prospects.